Plastic optical fiber immunosensor for fast detection of sulfate-reducing bacteria. (September 2018) - Lopes, Rafaela N.; Rodrigues, Domingos M.C.; Allil, Regina C.S.B.; Werneck, Marcelo M.
Abstract: Sulfate-reducing bacteria (SRB) are considered one of the oldest forms of microorganism that date back about 3.5 billion years and are common in anaerobic environments such as oil wells. SRB, in their metabolic process, produce hydrogen sulfide that contaminates the oil and is extremely toxic to humans, besides being one of the main causes of corrosion in the pipes. This paper presents a fast response-time biosensor, made of 1-mm diameter plastic optical fiber (POF) to detect SRB in production water. The physical principle for the operation is the interaction of the measurand with a curved waveguide based on the changes of the refractive index of the medium. The POF probes were functionalized with antibody anti-SRB and tested with Desulfovibrio alaskensis concentrations of 10 4, 10 6 and 10 8  MPN/mL (most probably number per mL). The optoelectronic setup consists of an 880 nm LED connected to a U-shaped probe. The system responded in about 30 min for concentrations of 10 4, 10 6 and 10 8  MPN/mL, encouraging an optimization of the sensitivity to read concentration of 10 3  MPN/mL or smaller. To the best of our knowledge, this is the first sensor to date capable to detect SRB with such small-time response.